EVALUASI STATUS HARA DAN PENYUSUNAN REKOMENDASI PEMUPUKAN DI PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq.) SEMBAWA BANYUASIN - Airiyani, Mey Linda; Hermawan, Agus; Fadli, Bori Heria; Yanti, Anita Andri (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Oil palm productivity can be increased by optimizing the availability of nutrients in the soil. Evaluation of nutrient status can be done to determine the level of nutrient availability for plants and as a basis for compiling site-specific fertilizer recommendations. This study aimed to evaluate the soil nutrient status in oil palm plantations at SMK PPN Sembawa Banyuasin and to compile fertilizer dose recommendations according to plant nutrient needs and nutrient availability in the soil. Analysis of chemical and physical properties of the soil was carried out at the Analytical Laboratory of PT. Binasawit Makmur Palembang. The parameters observed were pH, C-Organic, N, P, K, CEC, Al-dd and Soil Texture. This study used a detailed survey method on an area of 5 ha. Soil sampling was carried out at 5 observation points at a depth of 0-30 cm. The results of the study showed that the soil nutrient status at the research location had acidic soil pH conditions, low organic carbon, very low to low availability of N, P, K nutrients and low soil CEC. The soil texture class at the study location was Dusty Clay Loam. The low availability of nutrients at the study location caused the production of oil palm plants to be less than optimal. The calculation of the recommended fertilizer dose for 14-year-old oil palm plants at the study location was, with an average of 225.75 kg of Urea/ha/year or 1.83 kg/tree/year, SP-36 as much as kg/ha/year or 1.42 kg/tree/year, and KCl as much as 226.65 kg/ha/year or 1.83 kg/tree/year.